Manajemen Persembahan dalam Liturgi Pemakaman:Tinjauan Praktik dan Teologi dalam GERMITA - Bungkaes, Yerlin (PARADOSI: Jurnal Teologi Praktika, 2025)
This study examines the theological meaning and management practices of offerings in funeral liturgies at the Evangelical Christian Church in Talaud (GERMITA), focusing on the Maranatha Mangaran Congregation. While offerings are not officially included in GERMITA's funeral liturgy, this practice is implemented in the Maranatha Mangaran Congregation with significant results. A qualitative descriptive-analytical approach was employed to explore this phenomenon through interviews, observations, and document analysis. The findings indicate that offerings in funeral liturgies hold theological significance as expressions of gratitude to God and practical benefits in alleviating the financial burden on grieving families and strengthening congregational solidarity. This study suggests that church leaders consider integrating this practice into liturgical arrangements for greater relevance and meaning.